Memahami Perilaku Makan staf Universitas : Interaksi antara Pendidikan, Kelaparan, dan Indeks Massa Tubuh (BMI) - Undarwati, Anna; Pratiwi, Pradipta Christy; Nuzulia, Siti (Program Studi Psikologi UIN Sunan Ampel Surabaya, 2026)
Busy university staff often struggle to maintain a balanced diet which leads to health risks. This study investigated how education level, hunger, and Body Mass Index (BMI) influence food choices. A total of 109 university staff were invited to record their educational level, hunger and BMI and then the food choice using the Fake Food Buffet. General Linear Model analysis revealed the main effect of BMI significantly affected healthy food choices, F (1, 89) = 4.095, p = 0.46, partial ƞ2=.044, while hunger, (p =.057) and education level did not (p = .174). Importantly, a significant interaction was found between hunger and BMI, , F(1, 89) = 4.545, p = .036, partial ƞ2= .049, β = -14.130, 95% CI [-27.364, - .897] . While participants generally preferred healthy options, those with higher BMI chose significantly healthier foods overall; however, this pattern reversed when they were hungry, leading to poorer choices. Future studies might examine other personal factors, such as personality toward healthy food choices.